Interaction with PALB2 Is Essential for Maintenance of Genomic Integrity by BRCA2. - Suzanne A Hartford; Rajanikant Chittela; Xia Ding; Aradhana Vyas; Betty Martin; Sandra Burkett; Diana C Haines; Eileen Southon; Lino Tessarollo; Shyam K Sharan (PLoS Genetics)
Human breast cancer susceptibility gene, BRCA2, encodes a 3418-amino acid protein that is essential for maintaining genomic integrity. Among the proteins that physically interact with BRCA2, Partner and Localizer of BRCA2 (PALB2), which binds to the N-terminal region of BRCA2, is vital for its function by facilitating its subnuclear localization. A functional redundancy has been reported between this N-terminal PALB2-binding domain and the C-terminal DNA-binding domain of BRCA2, which undermines the relevance of the interaction between these two proteins. Here, we describe a genetic approach to examine the functional significance of the interaction between BRCA2 and PALB2 by generating a knock-in mouse model of Brca2 carrying a single amino acid change (Gly25Arg, Brca2G25R) that disrupts this interaction. In addition, we have combined Brca2G25R homozygosity as well as hemizygosity with Palb2 and Trp53 heterozygosity to generate an array of genotypically and phenotypically distinct mouse models. Our findings reveal defects in body size, fertility, meiotic progression, and genome stability, as well as increased tumor susceptibility in these mice. The severity of the phenotype increased with a decrease in the interaction between BRCA2 and PALB2, highlighting the significance of this interaction. In addition, our findings also demonstrate that hypomorphic mutations such as Brca2G25R have the potential to be more detrimental than the functionally null alleles by increasing genomic instability to a level that induces tumorigenesis, rather than apoptosis.